Pedagogical Characteristics of Organizing the Student Community in the Organization and Management of Educational Work Processes in Higher Education Institutions - Dadagoziev, Muzaffar Rakhnomoyevich (Researchparks Publishing, 2023)
This article analyzes the pedagogical features of organizing the student team in the organization and management of educational work processes in higher education institutions.